Smoking among school-going adolescents in selected secondary schools in Peninsular Malaysia- findings from the Malaysian Adolescent Health Risk Behaviour (MyaHRB) study. Issue 1 (December 2017) - Lim, Kuang; Lim, Hui; Teh, Chien; Kee, Chee; Khoo, Yi; Ganapathy, Shubash; Jane Ling, Miaw; Mohd Ghazali, Sumarni; Tee, Eng
Abstract Background A multitude of studies have revealed that smoking is a learned behaviour during adolescence and efforts to reduce the incidence of smoking has been identified as long-term measures to curb the smoking menace. The objective of this study was to determine the prevalence as well as the intra and inter-personal factors associated with smoking among upper secondary school students in selected schools in Peninsular Malaysia. Methods A study was carried out in 2013, which involved a total of 40 secondary schools. They were randomly selected using a two-stage clustering sampling method. Subsequently, all upper secondary school students (aged 16 to 17 years) from each selected school were recruited into the study. Data was collected using a validated standardised questionnaire. Results This study revealed that the prevalence of smoking was 14.6% (95% CI:13.3–15.9), and it was significantly higher among males compared to females (27.9% vs 2.4%, p < 0.001). Majority of smokers initiated smoking during their early adolescent years (60%) and almost half of the respondents bought cigarettes themselves from the store. Multivariable analysis revealed that the following factors increased the likelihood of being a current smoker: being male (aOR 21. 51, 95% CI:13.1–35), perceived poor academic achievement (aOR 3.42, 95% CI:1.50–7.37) had one or both parents who smoked (aOR 1.80, 95% CI:1.32–2.45; aOR 6.50, 95 CI%:1.65–25.65), and always feeling lonely (aOR 2.23, 95% CI:1.21–4.43). In contrast, respondents with a higher religiosity score and protection score were less likely to smoke (aOR 0.51, 95% CI:0.15–0.92; aOR 0.71, 95% CI 0.55–0.92). Conclusion This study demonstrated that the prevalence of smoking among Malaysian adolescents of school-going age was high, despite implementation of several anti-smoking measures in Malaysia. More robust measures integrating the factors identified in this study are strongly recommended to curb the smoking epidemic among adolescents in Malaysia.